How To Forecast Islamic Bank Profitability? - Ferieka, Hendrieta; Meutia, Meutia; Taqi, Muhamad; Lestari, Tri (IJOSMAS, 2025)
In governmental and private institutions, meticulous planning is paramount, given its pivotal role in affording a grace period for deliberation spanning years to hours. Forecasting is an indispensable tool in enhancing the efficacy and efficiency of such planning endeavors by projecting future occurrences through the meticulous analysis of historical data and its extrapolation into future contexts. Notably, forecasting provides a solid foundation for informed decision-making within economic planning. This study aims to address the following inquiries: 1) How is the liquidity ratio forecasting model developed using the ARIMA Box-Jenkins method at Bank Syariah Mandiri? 2) Based on the optimal forecasting model, What are the forecasted outcomes of the liquidity ratio utilizing the ARIMA Box-Jenkins method at Bank Syariah Mandiri for the forthcoming year? As a quantitative approach, the study utilizes secondary data from Bank Syariah Mandiri’s financial statements from January 2017 to November 2020, comprising 47 data points. Subsequently, forecasting is conducted for the period December 2020 to November 2021, encompassing one year. The findings reveal that the optimal forecasting model for the liquidity ratio at Bank Syariah Mandiri is the ARIMA (11,1,1) model for the Cash Ratio, projecting a liquidity capability of 130%. This outcome underscores the robust health of Bank Syariah Mandiri’s liquidity position. Moreover, the ARIMA (1,1,8) model for the financing-to-deposit ratio forecasts a liquidity capability of 77.4%, indicative of a healthy liquidity status. Finally, the ARIMA (3,1,3) model for the Loan to Asset Ratio forecasts a liquidity capability of 68.8%, affirming the institution’s sound liquidity position.